Incremental Net Benefit and Incremental Cost-Effectiveness Ratio of COVID-19 Vaccination Campaigns: Systematic Review of Cost-Effectiveness Evidence - Giuseppe Santoli; Mario Cesare Nurchis; Giovanna Elisa Calabrò; Gianfranco Damiani (Vaccines, 2023)
SARS-CoV-2 vaccination has been the most effective tool to prevent COVID-19, significantly reducing deaths and hospitalizations worldwide. Vaccination has played a huge role in bringing the COVID-19 pandemic under control, even as the inequitable distribution of vaccines still leaves several countries vulnerable. Therefore, organizing a mass vaccination campaign on a global scale is a priority to contain the virus spread. The aim of this systematic review was to assess whether COVID-19 vaccination campaigns are cost-effective with respect to no vaccination. A systematic literature search was conducted in the WHO COVID-19 Global literature database, PubMed, Web of Science, Embase, and Scopus from 2020 to 2022. Studies assessing the COVID-19 vaccination campaign cost-effectiveness over no vaccination were deemed eligible. The “Drummond’s checklist” was adopted for quality assessment. A synthesis of the studies was performed through the “dominance ranking matrix tool”. Overall, 10 studies were considered. COVID-19 vaccination was deemed cost-effective in each of them, and vaccination campaigns were found to be sustainable public health approaches to fight the health emergency. Providing economic evaluation data for mass vaccination is needed to support decision makers to make value-based and evidence-based decisions to ensure equitable access to vaccination and reduce the COVID-19 burden worldwide.